Threshold Concept of Pro-inflammatory Markers in Patients with Acne Vulgaris - Muhammad, Marwa S.; Hameed, Rana M.; Abdullhassan, Ali T. (Scientific Journal of Medical Research, 2022)
Acne vulgaris is an inflammatory condition of the pilosebaceous follicles that has no known cause. Hyperplasia of sebaceous glands and increased sebum output, hypercornification of pilosebaceous duct, aberrant colonization, notably by P. acnes, and inflammation all play a role in the etiology of acne vulgaris. The involvement of oxygen-free radicals and antioxidant enzymes in the aetiopathogenesis of acne vulgaris has been the subject of recent research. When antioxidant enzymes fail to protect cell and organelle membranes from oxidative damage, oxygen-free radicals cause lipid peroxidation. Oxidative stress affects all biological components by attacking lipids, proteins, and DNA. Among these illnesses, lipid damage caused by oxidative stress-induced lipid peroxidation is particularly significant to acne. The oxidative lipid breakdown in the skin, which is not merely a byproduct of the acne process, was proposed as the chemical etiology of acne. The lipid peroxidation results, lipid peroxides, can be both a cause and an acnegenic agent. This lipid peroxidation notion is supported by a study that shows lipid peroxidation occurs in acne and that site-specific free radical damage and lipid peroxidation products may be involved in the initiation of inflammation. Because the etiology and pathogenesis of acne are poorly known, and no single, major cause has been discovered, this paper was aimed to review the background documents in the scientific literature and focus on the following Question: Which Particularly pro-inflammatory substance might derive and consequence of acne? How could be improve the knowledge regarding the potential therapeutic target of Antioxidants in the regulation of oxidative stress of acne patients?